FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRE-EKLAMSIA PADAHAMIL DI POLI KEBIDANAN RUMAH SAKIT TINGKAT II ISKANDAR MUDA BANDA ACEH TAHUN 2014 - Fithriany Fithriany; Fitri Susana; Cut Yuniwati (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
Based the data obtained in Poly Midwifery of Grade II Hospital of IskandarMuda Banda Aceh, obtained that in 2013, of amount of pregnancy was 3.787, found 44 persons (1,16%) of pregnant mother havehypertension, as many 106 (2,79%) of pregnant mothers have severe pre-eklampsia and 2 (0,05%) ofpregnant mothers have eklampsia. Whereas period of 2014, of 3.188 of pregnant mothers who came to visit to Poly Midwifery of Grade II Hospital of IskandarMuda Banda Aceh, was 49 (1,53%) have hypertension, as many 126 persons (3,95%) have severe pre-eklampsia and as many 4 persons (0,15%) have eklampsia.Purpose of Study: To find out factors related to pre-eklampsia in pregnant mother in Poly-Midwifery of Grade II Hospital of IskandarMuda Banda Aceh, period of January up to December 2014.Method of Study: This study is in analytical survey by cross sectional approach, it was conducted in May 27th up to June 1st, 2015, population in this study was whole pregnant mothers who came to visited to Poly-Midwifery of Grade II Hospital of IskandarMuda Banda Aceh, January up to December 2014 periods,amounted to 3.188 persons, where sampling technique was using random sampling that taken randomly was 97 persons, the data is processed and analysed using chi-square (x2) test.Results of Study: There was correlation age to pre-eklampsia in pregnant mother with p=0,017 (p<0,05), there was correlation parity to pre-eklampsia in pregnant mother with p=0,021 (p<0,05), there was correlation history of hypertension to pre-eklampsia in pregnant mother with p=0,035 (p<0,05)Conlusion and Suggestion: There was correlation between age, parity and history of hypertension to pre-eklampsia in pregnant mother, expected to midwife for can give midwifery care to pregnant mother by pre-eklampsia so that may decrease the illness and death rates effect of pre-eklampsia.